User-centered web accessibility: recommendations for ensuring access to government information for older adults - Idrobo Cruz, Claudia Sofía; Martínez Flor, Ember Ubeimar; Vidal Caicedo, Maria Isabel (Ingeniería Solidaria, 2023)
Introduction: This article is the result of the research project “User-Centered Web Accessibility: Recommendations for Ensuring Access to Governmental Information for Older Adults”, developed at the University of Cauca-Colombia in 2023. Problem: Despite the importance of web accessibility, web pages are not adapting to the evolution of web accessibility proposed by the international consortium, which can limit access for users with physical and/or cognitive limitations. Objective: This article presents a set of recommendations for the design and development of government websites specifically for older adults, to ensure access to government information and take into account their health, physical, and mental condition. Methodology: A relationship is established between the limitations of older adults and the recommendations of the Web Content Accessibility Guidelines (WCAG) 2.2, with the aim of proposing specific design and development guidelines for government websites to counteract a specific limitation. Results: The implementation of these recommendations will allow government portals to have greater acceptance among older adult users. In addition, a case study was conducted in which these recommendations were validated and adjusted, which allowed for access to government information as a means of protecting fundamental rights. Conclusion: This article highlights the importance of web accessibility and proposes specific recommendations for the design and development of accessible government websites for older adults. Originality: This article presents a specific approach to web accessibility for older adults and proposes recommendations that differ from WCAG guidelines. Limitations: The proposed recommendations focus on web accessibility for older adults and do not address the limitations of other groups with physical and/or cognitive limitations. In addition, they were validated and adjusted in a specific case study and may require additional adjustments in other contexts.